Eco-minimalism : the antidote to eco-bling - Liddell, Howard (London : Riba, 2008)
This book highlights more realistic and cost effective approaches to going 'green' by showcasing 'eco-minimalism' - a good-housekeeping approach to ecological building design and specification, concentrating on less glaringly obvious strategies such as insulation, draught-proofing and the use of healthy materials.
boek